Resposta da soja a adubação em solo de várzea e efeito residual em arroz irrigado - Londero, Guilherme Tombesi (2012)
Currently, the soybean crop has been used as an alternative of rotation with rice, replacing fallow management in the control of red rice. Thus, the differences seen in terms of fertility between the two cultures, it is believed that the responses to fertilizers can advantage the performance of soybean that is most demanding in terms of nutrients, mainly potassium and phosphorous than rice crop, and then verify the possible residual effects on rice. The residual effect depends of soil type, of the quantity of nutrients applied and productivity of crop before cultivated. Therefore, the objectives of this study were to assess the application response to increasing doses of potassium (K), phosphorus (P) or limestone on soybean in a lowland soil from georeferenced points of precision agriculture and assess the residual effect of fertilizer potassium (K), phosphorus (P) or limestone in soybean phytotechnical on parameters of rice in succession. Two experiments were conducted in the lowland systematically, the first experiment carried out in two consecutive years with soybean and the second experiment with rice crop in rotation with soybean. The treatments for each element were 0, 30, 60, 90 kg of K2O; 0, 30, 60, 90 of kg P2O5 and 0, 1000, 2000, 4000 kg of limestone to soybean and subsequent implantation of rice in succession on each treatment. The results showed that fertilization and liming influenced positively the soybean, but was not observed significant residual effect of fertilization on rice crop.